Application of the Mathematics Curriculum in Intan Cendekia Islamic Kindergarten at Mataram City - Lukman, Lukman; Hastuti, Intan Dwi; Junaidin, Junaidin; Gani, Arsyad Abd. (JTAM (Jurnal Teori dan Aplikasi Matematika), 2021)
The purpose of this study was to describe the application of the Mathematics Curriculum at Intan Cendekia Islamic Kindergarten in Mataram City. The research utilized descriptive qualitative research and three teachers and one principal as research subjects. Data collection was carried out using observation, interviews, and documentation. The data that has been collected was analyzed using qualitative descriptive data analysis techniques, which were carried out continuously with data analysis activities, namely: data reduction, data display, and conclusion draining/verification. The results of the study show that the application of the mathematics curriculum in the kindergarten consists of planning mathematics learning, implementing mathematics learning, and assessing mathematics learning. Learning planning starts from preparing curriculum planning which consists of planning learning methods, planning space and plays centers, and planning learning process documents. The implementation of mathematics learning with the play method and the content of the initial mathematical concepts, namely matching, grouping, serialization, geometry and numbers. While for assessment applied observation assessment, an anecdotal record of performance assessment, and product assessment.